INVOLVEMENT OF WORLDWIDE FLAX GENETIC RESOURCES FROM VIR’S COLLECTION IN THE DEVELOPMENT OF CULTIVARS IN TOMSK - G. A. Popova (Труды по прикладной ботанике, генетике и селекции, 2018)
Twenty-six flax accessions of diverse ecogeographic origin from VIR’s collection (4 from Russia, 3 from Kazakhstan, 2 from Mongolia, 2 from Portugal, 1 from Spain, and 14 from France) were evaluated in 2009-2011 at the experimental field of the Siberian Institute of Agriculture and Peat located in the subtaiga zone of Western Siberia with continental climate. Using the two-factor variance and correlation analyses, the effect of genotypes andenvironments on the expression of plant characters and correlations between them were studied. The accessions with best agronomic traits - k -1338 (Kazakhstan), k-1436 (Altai province), k-1439 (Kazakhstan), k-6085 (Portugal), k-7454 (France), k-7359 (Portugal), k- 7460 (France), k-7470 (France), and k-8289 (France) - were recognized as promising source material and were involved in the breeding process as paternal parent forms. Twenty hybrid combinations were obtained, and 440 plants were placed into the screening nursery.